التكييف الفقهي لتعمد نقل مرض وباء فيروس كورونا Covid-19 - القرني، عزيزة بنت سعيد بن معيض (مؤسسة البحوث والدراسات الفقهية وعلوم القرآن الكريم الوقفية, 2021)
يعدُّ الوباء مرضًا يصيب عددًا كبيرًا من الناس في منطقة واحدة في مدة قصيرة من الزمن، وقد يطلق عليه الجائحة، وفيروس كورونا (COVID-19) هو التهاب في الجهاز التنفسي بسبب فيروس تاجي جديد، وتعدُّ الصين وبالتحديد مدينة ووهان الصينية هي المنشأ الأساسي للفيروس، وهو سريع الانتشار شديد العدوى. وقد تم تحديد تدابير وقائية للحد من انتشاره لما فيه من الإضرار بالآخرين وقد جاءت الشريعة الإسلامية بتحريم الإضرار بهم. وإن تعمد نقل مرض وباء كورونا ونشره في المرافق العامة والأسواق يمكن أن يكون نوعًا من أنواع الحرابة والإفساد في الأرض، أما إذا نقل المرض بدون قصد فمات المنقول إليه فيعدُّ من قبيل القتل الخطأ، يجب عليه الضمان، وإن لم يمت فإنه يعزر حسب ما يراه الإمام، ثم إن الراجح في نقل مرض كورونا عمدًا لقتل شخص أو أشخاص يعدُّ من قبيل القتل العمد. وإن المسؤولية هي الالتزام القانوني نتيجة إتيانه فعلً أو امتناعه عن فعل، يشكل ضررًا على المريض، يستوجب عقوبة شرعية من قصاص أو تعزير أو ضمان وفق ما قررته الشريعة الإسلامية في الأمور الجنائية أو الطبية، وهذه المسؤولية الطبية منصوص عليها في الشريعة الإسلامية باسم الضمان، ومن موجبات المسؤولية الطبية الاعتداء وعدم اتباع الأصول العلمية للمهنة، ويعد الممارس الصحي مؤتمنًا على حياة المريض، فإذا تعمد القيام بفعل يوجب الضرر بالمريض أو غيره من الممارسين الصحيين مع علمه بالآثار المترتبة على فعله، فإنه موجب للمسؤولية من قصاص أو دية.
An epidemic is a disease that affects a large number of people in one area in a short period of time, and it may be called a pandemic. Coronavirus (COVID-19) is an infection in the respiratory system due to a new type of coronavirus. China, specifically the Chinese city of Wuhan, is the primary origin of the virus, noting that the virus is rapidly spreading and highly contagious. Thus, preventive measures have been identified to limit its spread because it harms others, and Islamic law prohibits harming them. The deliberate transmission of the Corona epidemic disease, and it’s spread in public facilities and markets could be a kind of warfare and corruption on the ground. But if the disease was transmitted unintentionally, and then the transferee died, in this case, it is considered a wrongful killing, and he is obliged to guarantee. If he does not die, then he should be judged according to what the imam sees. Nevertheless, the most correct view if to intentionally transmit Corona disease in order to kill a person or people is considered as intentional killing. Responsibility is commitment as a result of committing an act or refraining from doing an act that constitutes harm to the patient, which requires a Sharia punishment, such as retribution, discretion, or guarantee in accordance with what the Islamic Sharia has decided in the criminal or medical matters. This medical liability is stipulated in Islamic law in the name of insurance, noting that among the obligations of medical liability is assault and failure to follow the scientific principles of the profession. Hence, the health practitioner is considered entrusted with the life of the patient, thus, if he intends to perform an act that causes harm to the patient or other health practitioner with knowledge of the consequences of his action, then he is liable for punishment or money.
Keywords: الفقه الإسلامي -- الأمراض الوبائية -- فيروس كورونا "كوفيد-19" -- المسؤولية الطبية